The psilid Glycaspis brimblecombei in transition areas Biomes Amazon and Brazilian Savanna - Ribeiro Dias, Thaise Karla; Pires, Evaldo Martins; Wilcken, Carlos Frederico [UNESP]; Souza, Adilson Pacheco; Soliman, Everton Pires; Silva, Cala Cardoso (Univ Federal Campina Grande, 2017)
In the state of Mato Grosso, intensive forestry is in the initial phase covering less than 0.2% of the territory. Agribusiness boosted investments for the establishment of populations with forest species, especially the cultivation of Eucalyptus sp. Glycaspis brimblecombei (red gum lerp psillid) has become an important pest for eucalyptus cultivation in Brazil. The objective of this research was to report the occurrence of G. brimblecombei in the Mato Grosso State in transition areas Biomes Amazon and Brazilian Savanna. In June 2014, adults, egg masses and nymphs of redgum lerp psyllid were observed attacking these Myrtaceae in the cities of Sinop, Sorriso, Lucas do Rio Verde and Feliz Natal. The period that characterizes the dry season in the region is between May to October and due to the high temperatures and low precipitation rates favor the occurrence of this pest. This is the first record of G. brimblecombei in the North of Mato Grosso.
Keywords: Adults; Eucalyptus; immatures; occurence; pest